The Use of Figurative Languages on the Students' Poetry Semester V at FKIP Universitas HKBP Nommensen - Bertaria Sohnata Hutauruk (Journal of English Language and Culture, 2019)
This research discusses The Use of Figurative Languages on the Students’ Poetry Semester V at FKIP Universitas HKBP Nommensen. The problems of this research are (1) what types of figurative language used on the students’ poetry semester V at FKIP Universitas HKBP Nommensen Medan? (2) what figurative language is dominantly used on the students’ poetry  semester V at FKIP Universitas HKBP Nommensen Medan? The objectives of this research are to find out types of figurative language used on the students’ poetry semester V at FKIP Universitas HKBP Nommensen Medan and to figure out and analyze what figurative language is dominantly used on the students’ poetry  semester V at FKIP Universitas HKBP Nommensen Medan?To find out the answer of the problem in this research, the writer uses the related theories; they are Quinn (1982), McDonough and Shaw (1993), Gluckberg (2001), Alm-Arvius (2003), Lazar (2003), Ratumanan and Laurens (2003), Brown (2004), Harmer (2004), Heller (2006), Picken (2007), Keraf (2009), Creswell (2009), Arikunto (2010), Arnold and Von Hollander (2011), Dalman (2012), Dancygier and Sweetser (2014). This research is conducted with descriptive qualitative research where the subject and object is taken from the students’ poetry. The writer gets the data by observation and documenting. After the data had been collected, the writer finds out three types of figurative language on the students’ poetry: symbol, metaphors and personifications. In teaching poetry, every teacher needs to call upon a number of techniques and methods. If teachers of poetry disagree on the methods of teaching a certain poet, they must agree on goals: To put their students in touch with the mind of that poet. No doubt, it is known for every one that good poetry lessons occur in classrooms where young people are guided by responsive teachers who implement as well as they plan.Keywords: Figurative language, poetry, language